Safety after BBIBP-CorV (Sinopharm) COVID-19 Vaccine in Adolescents Aged 10–17 Years in Thailand - Saraiorn Thonginnetra; Kriangkrai Tawinprai; Krongkwan Niemsorn; Pathariya Promsena; Manunya Tandhansakul; Naruporn Kasemlawan; Natthanan Ruangkijpaisal; Narin Banomyong; Nanthida Phattraprayoon; Pisuttikan Rangkakulnuwat; Preeda Vanichsetakul; Teerapat Ungtrakul; et al. (Vaccines, 2022)
Coronavirus disease 2019 affected child health and impacted learning because of the resulting onsite school closures. This prospective cohort study included children aged 10–17 who received two 4 µg doses of BBIBP-CorV administered intramuscularly 21–28 days apart. To assess vaccine safety, 36,808 participants were then followed with paper- and web-based online questionnaire surveys that captured local and systemic reactogenicities following vaccine administration on days 1, 7, and 30. Among participants, 76% (27,880) reported reactogenicity within the first 24 h and 7 days following the first dose. Half (51.41%) of participants experienced pain at the injection site; the majority of cases were mild in severity. Injection site tenderness (37.93%) was another common local reaction. Fatigue (37.89%), myalgia (33.56%), and headache (26.76%) were the most common systemic reactions. On days 2–7 after the first dose, 25.85% of participants experienced adverse reactions. Following the second dose, reactogenicity was 7.6% and 1.09% within 24 h and between days 2–7. The majority of reactions were of mild to moderate severity. We report that two doses of the BBIBP-CorV caused mild to moderate side effects in adolescents in Thailand. The findings confirm the vaccine’s safety profile in this age group.